2001
DOI: 10.1128/aem.67.5.2056-2061.2001
|View full text |Cite
|
Sign up to set email alerts
|

Yeast Population Dynamics during the Fermentation and Biological Aging of Sherry Wines

Abstract: Molecular and physiological analyses were used to study the evolution of the yeast population, from alcoholic fermentation to biological aging in the process of "fino" sherry wine making. The four races of "flor" Saccharomyces cerevisiae (beticus, cheresiensis, montuliensis, and rouxii) exhibited identical restriction patterns for the region spanning the internal transcribed spacers 1 and 2 (ITS-1 and ITS-2) and the 5.8S rRNA gene, but this pattern was different, from those exhibited by non-flor S. cerevisiae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
74
0
7

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(83 citation statements)
references
References 16 publications
2
74
0
7
Order By: Relevance
“…The case of ALD6 is particularly interesting, where basal levels are higher under growth in 2% glucose in flor yeasts. Strain C is the most resistant to ethanol and acetaldehyde and the most abundant in the wineries from which these strains have been isolated (Esteve-Zarzoso et al, 2001). Moreover, it is the only one where there is no decrease in ALD6 mRNA levels after acetaldehyde addition under these conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The case of ALD6 is particularly interesting, where basal levels are higher under growth in 2% glucose in flor yeasts. Strain C is the most resistant to ethanol and acetaldehyde and the most abundant in the wineries from which these strains have been isolated (Esteve-Zarzoso et al, 2001). Moreover, it is the only one where there is no decrease in ALD6 mRNA levels after acetaldehyde addition under these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…for S. cerevisiae 'flor' yeast strains involved in the biological ageing of sherry wines (Jackson, 1994;Martínez et al, 1997a,b). These strains are different from those involved in the fermentation stage (Esteve-Zarzoso et al, 2001) and form a thin velum (film) on the surface of the wine. During biological ageing, yeast cells are affected by ethanol stress because the final fermentation product is supplemented with ethanol up to a final concentration of 15-15.5 • .…”
Section: Introductionmentioning
confidence: 96%
“…The high level of polymorphism in the structure of the nuclear and mitochondrial genomes found in different studies on natural populations has allowed the differentiation of closely related isolates 22,29,37 . Different authors 4,6,12,25 have found a greater genetic variability of the mitochondrial genome.…”
Section: Discussionmentioning
confidence: 99%
“…After the process is finished, wine is fortified to 15% (v/v) and it is put into oak barrels for storage. The process of biological ageing begins at this moment, using the "Solera" system [3].…”
Section: Introductionmentioning
confidence: 99%